Variable-Structure Approaches Analysis, Simulation, Robust Control and Estimation of Uncertain Dynamic Processes - Rauh, Andreas; Senkel, Luise (Mathematical Engineering, 2016)
This edited book aims at presenting current research activities in the field of robust variable-structure systems. The scope equally comprises highlighting novel methodological aspects as well as presenting the use of variable-structure techniques in industrial applications including their efficient implementation on hardware for real-time control. The target audience primarily comprises research experts in the field of control theory and nonlinear dynamics but the book may also be beneficial for graduate students.